Hubungan Kebiasaan Sarapan Pagi dan Status Gizi dengan Prestasi Belajar Siswa di Madrasah Ibtidaiyah Siti Mariam Banjarmasin Tahun 2023 - Mawaddah, Najah Marlina; Netty, Netty; Norfai, Norfai (Universitas Baiturrahim, 2024)
Nutritional fulfilment plays an important role for school-age children. Children who consume nutritious food regularly will be more assured of their health and fitness to carry out activities, so that they can achieve maximum learning achievement. This study aims to determine and analyse the relationship between breakfast habits and nutritional status with student learning achievement at Madrasah Ibtidaiyah Siti Mariam Banjarmasin in 2023. This type of research is quantitative using an analytical survey with a cross sectional approach. The sample size was 55 respondents and used simple random sampling technique. Data collection using a questionnaire. Statistical test analysis used is univariate analysis and bivariate analysis of chi-square test with 95% confidence level. Based on the results of statistical tests, there is a significant relationship between breakfast habits and learning achievement with ρ = 0.001 and there is a significant relationship between nutritional status and learning achievement ρ = 0.000. The relationship between breakfast habits, nutritional status and learning achievement can be an indicator for students to have breakfast regularly because it can improve learning achievement. It is recommended for schools to collaborate with the nearest public health centre to provide education about the importance of nutrition at school age comprehensively by involving the role of parents of these students.